Empathy and mental health distress in informal caregivers of dementia and stroke patients: a cross-sectional study - Jing Mei; Yi He; Jia Li; Fang Chen; Shihua Pan; Yang Xu; Huimin Sun (Scientific Reports)
Abstract Informal caregivers of patients with neurodegenerative diseases are confronted with significant psychological distress. However the role of empathy in their mental health distress remains understudied. This study addressed this gap by investigating the association between empathy and mental health outcomes with three groups (130 dementia caregivers, 130 stroke caregivers and 132 non-caregivers) through quantitative surveys. Measures included the Chinese Perceived Stress Scale (CPSS), Irritability, Depression, and Anxiety Scale (IDA), the Chinese Interpersonal Reactivity Index (IRI-C), and sociodemographic questionnaires. We found that dementia caregivers presented higher total empathy and depression scores than did stroke caregivers and non-caregivers. Stroke caregivers reported significantly greater perceived stress than did both groups. Among caregivers, cognitive empathy (IRI-C subscales) and positive affective empathy were inversely associated with the IDA and CPSS dimensions(e.g., depression, anxiety, irritability and perceived distress). Conversely, negative affective empathy was positively correlated with most psychological distress indicators. These findings highlight that cognitive empathy and positive affective empathy may serve as protective factors against mental health issues in informal caregivers, whereas negative affective empathy exacerbates psychological burden. Interventions targeting empathy enhancement (particularly cognitive components) could mitigate caregiver distress. Future research should explore causal mechanisms and test empathy-focused interventions in geriatric care settings.